2023
DOI: 10.1021/acs.est.2c09389
|View full text |Cite
|
Sign up to set email alerts
|

The Minus Approach Can Redefine the Standard of Practice of Drinking Water Treatment

Abstract: Chlorine-based disinfection for drinking water treatment (DWT) was one of the 20th century’s great public health achievements, as it substantially reduced the risk of acute microbial waterborne disease. However, today’s chlorinated drinking water is not unambiguously safe; trace levels of regulated and unregulated disinfection byproducts (DBPs), and other known, unknown, and emerging contaminants (KUECs), present chronic risks that make them essential removal targets. Because conventional chemical-based DWT pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…Nanofiltration (NF) has obtained a variety of applications in the environmental fields, including softening of hard water, removal of natural organic matter , and emerging contaminants from drinking water, separation of sulfate from chloride for zero liquid discharge, and more recently lithium extraction from natural brines. In these applications, the requirement for the highly selective separation of some solutes from others could perfectly be satisfied by the rejection characteristics of NF membranes. The membrane properties, however, must be well tuned based on the rejection mechanisms, including steric hindrance effect, electrostatic effects, etc. Taking the lithium–magnesium separation as an example, if the effective pore size of an NF membrane is in between the sizes of hydrated ions of lithium (0.382 nm) and magnesium (0.428 nm), effective separation of the two types of ions can be achieved by the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofiltration (NF) has obtained a variety of applications in the environmental fields, including softening of hard water, removal of natural organic matter , and emerging contaminants from drinking water, separation of sulfate from chloride for zero liquid discharge, and more recently lithium extraction from natural brines. In these applications, the requirement for the highly selective separation of some solutes from others could perfectly be satisfied by the rejection characteristics of NF membranes. The membrane properties, however, must be well tuned based on the rejection mechanisms, including steric hindrance effect, electrostatic effects, etc. Taking the lithium–magnesium separation as an example, if the effective pore size of an NF membrane is in between the sizes of hydrated ions of lithium (0.382 nm) and magnesium (0.428 nm), effective separation of the two types of ions can be achieved by the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant research efforts in the field of DBPs, the understanding of their formation in chlorinated drinking water remains incomplete. It has been observed that the formation of DBPs is affected by certain environmental parameters such as the interaction with various types of NOM, temperature, and pH.…”
Section: Introductionmentioning
confidence: 99%
“…During oxidative water treatments, dissolved organic matter (DOM) serves as not only the primary sink for the dosed oxidant , but also the primary precursor of DBPs. Previous studies have shown that changes of DOM characteristics closely correlate with DBP formation, , and the redox-active moieties of DOM compete directly for the oxidant against MPs. Therefore, monitoring the changes in DOM characteristics induced by oxidation is a feasible way to determine the appropriate oxidant dosage. , Currently, the surrogate indicators commonly employed to optimize the oxidant dosage include the dissolved organic carbon (DOC), UV absorbance at 254 nm (UV 254 ), and fluorescence index (FI). ,,, However, DOC cannot effectively indicate MP abatement and DBP formation due to limited organic mineralization. , In addition, although the spectroscopic surrogate indicators (UV 254 and FI) have been extensively adopted in oxidative water treatments and correlate well with MP abatement and DBP formation in lab-scale and full-scale experiments, ,, they just reflect the changes in the chromophoric moieties of DOM. Therefore, it is necessary to develop a new surrogate indicator to enhance the precision, reliability, and robustness of existing control systems for oxidative water treatments.…”
Section: Introductionmentioning
confidence: 99%